Healthcare utilization in Danish children with atopic dermatitis and parental topical corticosteroid phobia. Issue 2 (9th November 2020) - Gerner, Trine; Haugaard, Jeanette Halskou; Vestergaard, Christian; Deleuran, Mette; Jemec, Gregor Borut; Mortz, Charlotte Gotthard; Agner, Tove; Egeberg, Alexander; Skov, Lone; Thyssen, Jacob P.
Abstract: Background: Atopic dermatitis (AD) is a prevalent relapsing inflammatory skin disease. There is currently little knowledge about healthcare utilization and medication use along with parental corticosteroid phobia in relation to severity of pediatric AD. Objectives: To study the association between parental‐reported healthcare utilization, medication use, and topical corticosteroid phobia and pediatric AD severity. Methods: The study population included all children in Denmark with a diagnostic code of AD (ICD‐10 code, group L20) given at a hospital department of dermatology between 2014 and 2018. A questionnaire containing 158 response items was sent to the legal parents. We surveyed disease severity, AD treatment, corticosteroid phobia, and healthcare use along with other variables. Disease severity was assessed using the Patient‐Oriented Eczema Measure tool, and corticosteroid phobia was assessed using the Topical Corticosteroid Phobia (TOPICOP) score. Results: In total, 1343 (39%) parents completed the questionnaire and 95.3% were completed by the biological mother. Children's mean age was 8.9 ± 4.5 years, and 52.8% were boys. Severe AD was associated with a higher number of healthcare visits to GPs, private dermatologists, and hospital departments. Mean global TOPICOP score was 38.27 ± 19.9%. There was a significant inverse linear trend between global TOPICOP score and parental educational level ( P trend < .0005). Conclusions: The significant association between high global TOPICOP score and low parental educational level, resulting in delayed treatment of AD flares, indicates that improved family education ultimately may reduce healthcare expenses and burden of disease.